Gambaran Pelaksanaan Pelayanan Kesehatan Peduli Remaja (PKPR) Di Puskesmas Dupak Surabaya - Tamara Avilla (Universitas Airlangga, 2019)
Background: Adolescent health services is one of the government programs aimed at teenagers in Indonesia with the intention that teenagers have a comfortable place to grip or help deal with all sorts of teenage problems that are being faced. This PKPR is implemented in every Health Care. Purpose: the aims of this study was seen implementation  PKPR in Dupak Health Care, Surabaya. Methods: This study was conducted at Dupak Health Care, Surabaya using qualitative descriptive research with observation method and in-depth interview at Head of Dupak Health Care Surabaya, holder of UKBM program (The Effort of Health Community Based Services) in Health Care, PKPR program holder, and some teenagers working area of Health Care. Results: The results and discussion in this journal that describes the implementation of health care services adolescents at Puskesmas Dupak Surabaya Health Center by adjusting the reference of National Standard PKPR 2014 and in line with previous similar research. Conclusion: There is a mismatch between the implementation of PKPR and the national standard of health care for adolescents that is influenced by various factors.